Tomsk State University: Space-planning development concept - Grigoryeva, Elena; Kozmin, Alexei; Meerovich, Mark (project baikal, 2015)
The article features the space-planning development concept for National Research Tomsk State University and the subsequent sketch design. Together with extension of educational and laboratory area, the system of open exterior and interior public spaces is created for interpersonal communication, independent work, leisure, self-presentations, team building events, etc. One of the leading principles is preservation of the University historical heritage together with appliance of advanced architectural and spatial methods and integration of facilities built at different times into one complex.
Keywords: concept; University campus; spatial reorganization of the University; historical environment